A novel longitudinal interprofessional ambulatory training practice: the improving patient access care and cost through training (IMPACcT) clinic. Issue 3 (4th May 2021) - Block, Lauren; LaVine, Nancy A.; Martinez, Johanna; Strawser, Josiah; Lu, Celia; Cacace, Frank; Fornari, Alice; Conigliaro, Joseph; Coletti, Daniel J.
ABSTRACT: Few graduating health professionals choose primary care. Trainees satisfied with continuity ambulatory experiences are more likely to pursue primary care. The authors developed a longitudinal interprofessional ambulatory training program to improve team-based care and encourage primary care careers. The Improving Patient Access Care and cost through Training (IMPACcT) clinic, launched in 2016, includes physician, physician assistant, pharmacy, and psychology trainees. Residents, faculty, and interprofessional trainees complete "on-service" weeks together. Co-located administrative team members coordinate care and lead team "huddles." Interprofessional signout facilitates patient follow-up. The initial evaluation included process and quality indicators compared to the traditional resident practice. Learners reported increased perceived competence in interprofessional communication and teamwork after completing their training. Clinical quality outcomes suggested improved provider continuity and arrival rate compared to traditional resident practice (56.5% vs. 32.9%; 66.3% vs. 62.2%, p < .01). Patient satisfaction was higher in the IMPACcT clinic in the areas of coordinated care and team functioning. Ten of eighteen physician graduates in the program chose further training in primary care compared to 20 of 150 graduates not in the program (55.6% vs. 13.3%, p < .01). Implementing a longitudinal team-based ambulatory interprofessional training practice was associated with improved continuity of care and improved patient satisfaction indicators.